Enhanced dispersion and properties of a two-component epoxy nanocomposite using surface modified cellulose nanocrystals. (10th March 2017) - Peng, Shane X.; Shrestha, Shikha; Yoo, Youngman; Youngblood, Jeffrey P.
Abstracts: Epoxy nanocomposites reinforced with acetyl, hexanoyl, and dodecanoyl surface modified Cellulose Nanocrystals (CNC) were fabricated. Surface modified CNCs were dispersed in epoxy resin with a co-solvent. After complete removal of the co-solvent, a typical two component epoxy system was achieved where hardener was then added to cure the resin. Acetyl grafted CNC (CNC_a) and hexanoyl grafted CNC (CNC_h) both had good dispersion in cured epoxy as observed visually and through electron microscopy. Tensile modulus, tensile strength, and work of fracture of epoxy were improved with the addition of CNC_a and CNC_h. CNC_a reinforced epoxy had the highest increases in mechanical properties. Dodecanoyl grafted CNC (CNC_d) led to aggregation in the epoxy which led to insignificant changes in mechanical properties. The addition of CNC_a increased glass transition temperature (Tg ) of epoxy while CNC_h and CNC_d led to Tg depression. Graphical abstract: Highlights: A solvent free mixture of epoxy resin and Cellulose nanocrystal (CNC) was formulated using surface modified CNCs. Hexanoyl grafted CNCs had the best dispersion in epoxy compared to acetyl and dodecanoyl grafted CNCs. Acetyl grafted CNC improved Young's modulus, tensile strength, and work of fracture of neat epoxy. Hexanoyl and dodecanoyl grafted CNCs led to decreases, while acetyl grafted CNC led to an increase in Tg .